Multi-objective Optimal Operation of Centralized Battery Swap Charging System with Photovoltaic - Yuanzheng Li; Yihan Cai; Tianyang Zhao; Yun Liu; Jian Wang; Lei Wu; Yong Zhao (Journal of modern power systems and clean energy, 2022)
Electric vehicles (EVs) are widely deployed throughout the world, and photovoltaic (PV) charging stations have emerged for satisfying the charging demands of EV users. This paper proposes a multi-objective optimal operation method for the centralized battery swap charging system (CBSCS), in order to enhance the economic efficiency while reducing its adverse effects on power grid. The proposed method involves a multi-objective optimization scheduling model, which minimizes the total operation cost and smoothes load fluctuations, simultaneously. Afterwards, we modify a recently proposed multi-objective optimization algorithm of non-sorting genetic algorithm III (NSGA-III) for solving this scheduling problem. Finally, simulation studies verify the effectiveness of the proposed multi-objective operation method.